Effect of AB2-based alloy addition on structure and electrochemical properties of La0.5Pr0.2Zr0.1Mg0.2Ni2.75Co0.45Fe0.1Al0.2 hydrogen storage alloy - 卢照 覃铭 蒋卫卿 卿培林 刘淑辉 (Journal of rare earths, 2013)
TheLa0.5Pr0.2Zr0.1Mg0.2Ni2.75Co0.45Fe0.1Al0.2（M0 and Zr0.65Ti0.35（Mn0.2V0.2Cr0.15Ni0.45）l.76 （M2） hydrogen storage alloys were prepared by inductive melting. In addition, the M1＋30 wt.%M2 composites were successively prepared by using high-energy ball milling technology. From the X-ray diffraction （XRD） analysis, it was found that M1 and M2 alloys still retained their respective main phases in the MI＋30 wt.%M2 composites. The scanning electron microscopy （SEM） and energy dispersive spectroscopy （EDS） indicated that the decrease in discharge capacity of MI and M2 alloy electrodes was ascribed to the oxidation-dissolution of La, Pr, Mg and Ti, Mn, V, Cr active elements, respectively. The electrochemical studies showed that the M1＋30 wt.%M2 composite electrode ball milling for 5 rain exhibited excellence cyclic stability （92.3%） after 80 charge/discharge cycles, which was higher than 77.7 % and 85.6% of MI and M2 alloy electrodes, respectively. Moreover, at the discharge current density of 1200 mA/g, the high rate dis- charge ability （HRD） of the M1＋30 wt.%M2 composite electrode increased from 61.5% （5 rain） to 70.3% （10 rain）. According to the linear polarization, Tafel polarization and cyclic voltammograms （CV）, the electrochemical kinetics of hydrogen reaction on the sur- face of the electrode and hydrogen diffusion rate in the bulk of alloy were also improved in the ML＋30 wt.%M2composite with in- creasing ball milling time.